2020
DOI: 10.25225/jvb.20028
|View full text |Cite
|
Sign up to set email alerts
|

On the role of (and threat to) natural history museums in mammal conservation: an African small mammal perspective

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 200 publications
(192 reference statements)
0
7
0
Order By: Relevance
“…Another factor causing the misplacement of the Rufous Sengi in previous phylogenetic trees is the generally low amount of available genetic data from sengis from eastern Africa as most previous research focused on the southern part of the continent (see references in Introduction). These facts again strengthen the necessity of a collection of fresh samples from understudied areas directly in the field (together with as much additional data as possible), as well as the need for linking physical voucher specimens to GenBank sequences, especially if they should be used for genomic analyses of biodiversity and its evolution (reviewed by Ferguson, 2020; see Heritage et al, 2020, for a recent example in sengis).…”
Section: Discussionmentioning
confidence: 90%
“…Another factor causing the misplacement of the Rufous Sengi in previous phylogenetic trees is the generally low amount of available genetic data from sengis from eastern Africa as most previous research focused on the southern part of the continent (see references in Introduction). These facts again strengthen the necessity of a collection of fresh samples from understudied areas directly in the field (together with as much additional data as possible), as well as the need for linking physical voucher specimens to GenBank sequences, especially if they should be used for genomic analyses of biodiversity and its evolution (reviewed by Ferguson, 2020; see Heritage et al, 2020, for a recent example in sengis).…”
Section: Discussionmentioning
confidence: 90%
“…from the Simien Mountains (Craig et al 2020), the updated Ethiopian shrew list consists of at least 31 species (two Suncus and 29 Crocidura) with 13 endemic Crocidura species. This checklist is certainly not final as there are indications for other taxonomically unresolved groups, including specimens that do not correspond to any recognized species (our unpublished data), suggesting a need for further sampling and comparative research (as also found in rodents (Bryja et al 2019a); see also Ferguson et al 2020). This high level of endemism is undoubtedly linked to the substantial heterogeneity of geomorphology and vegetation type in this mountainous African country (Lillesø et al 2011, Bryja et al 2019a, and also to the biogeographical position of the Ethiopian Highlands at the entrance to Africa from south-western Asia, notably the Arabian Peninsula.…”
Section: Diversity Of Shrews In Ethiopiamentioning
confidence: 99%
“…Ethiopian rats as a model for evolutionary research Ethiopian rats of the genus Stenocephalemys usually form the most abundant members of small mammal assemblages in the Ethiopian Highlands (see e.g. recent studies of Kostin et al 2019, 2020, Craig et al 2020. They are also important agricultural pests (Meheretu & Leirs 2019, Welegerima et al 2020 and reservoirs of potentially harmful hantaviruses (Meheretu et al 2012).…”
Section: Stenocephalemys Ruppi Van Der Straeten and Dieterlen 1983mentioning
confidence: 99%